Baseline Renal Function Predicts Hyponatremia in Liver Cirrhosis Patients Treated with Terlipressin for Variceal Bleeding - Sung Eun Kim; Dong Min Jung; Ji Won Park; Yeonmi Ju; Bohyun Lee; Hyoung Su Kim; Ki Tae Suk; Myoung Kuk Jang; Sang Hoon Park; Jun Goo Kang; Jae Seung Soh; Hyun Lim; et al. (Gastroenterology Research and Practice)
Objectives. Terlipressin is safely used for acute variceal bleeding. However, side effects, such as hyponatremia, although very rare, can occur. We investigated the development of hyponatremia in cirrhotic patients who had acute variceal bleeding treated with terlipressin and the identification of the risk factors associated with the development of hyponatremia. Design and Methods. This retrospective, case-control study investigated 88 cirrhotic patients who developed hyponatremia and 176 controls that did not develop hyponatremia and were matched in terms of age and gender during the same period following terlipressin administration. Results. The overall change in serum sodium concentration and the mean lowest serum sodium concentration were 3.44 ± 9.55 and 132.44 ± 8.78 mEq/L during treatment, respectively. Multivariate analysis revealed that baseline serum sodium was an independent positive predictor, and the presence of baseline serum creatinine, HBV, DM, creatinine, and shock on admission was independent negative predictors of hyponatremia (P<0.05). Conclusion. The presence of HBV, DM, the baseline serum sodium, shock on admission, and especially baseline creatinine may be predictive of the development of hyponatremia after terlipressin treatment. Therefore, physicians conduct vigilant monitoring associated with severe hyponatremia when cirrhotic patients with preserved renal function are treated with terlipressin for variceal bleeding.